Bionomics of Mosquitoes (Diptera: Culicidae) to Design a Comprehensive Control Program in Important Tourism Centers of Fars Province, Southern Iran - Masoumeh Amin; Mohsen Kalantari; Saideh Yousefi; Mozaffar Vahedi; Sorna Dabaghmanesh; Hamid Reza Ghorbani; Marzieh Shahriari Namadi; Parisa Amin (Shiraz University of Medical Sciences, 2024)
Background: The general purpose of this study was to investigate the species diversity and characteristics of the larval habitats of culicids in important tourism centers of Fars province to design a comprehensive program to control them.Methods: In a cross-sectional study conducted from April to the end of September 2021, the species diversity of mosquito larvae and the characteristics of larval habitats were investigated. Mosquito larvae were collected using the dipping method and the characteristics of larval habitats such as permanent or temporary habitat, water running, intensity of sunlight, vegetation, habitat floor, turbidity, natural or artificial were recorded according to the hydro ecological characteristics.Results: Totally, 8825 specimens were collected and identified from 9 selected locations in Marvdasht city and 6 selected locations in Maharloo wetland. Collected species were Culex pipiens (39.77%), Culex sinaiticus (3.80%), Culex quinquefasciatus (23.68%), Culiseta longiareolata (17.52%), Uranotaenia unguiculata (9.02%), and Anopheles stephensi (6.21%). Most specimens (79%) were collected from natural habitats. There is a significant difference between the number of collected mosquitoes with the permanent habitat, stagnant water, partial sunlight, vegetation, turbidity, and natural habitat (P<0.0001). The dominant species were Cx. pipiens (39.77%) and Cx. quinquefasciatus (23.68%).Conclusion: These species are potentially involved in the transmission of many pathogens to humans and domestic animals and should be extensively studied. The results of this study suggest that environmental factors play an important role in larvae's habitat preference.